2007
DOI: 10.1007/s11244-007-0331-7
|View full text |Cite
|
Sign up to set email alerts
|

The genesis and importance of oxide–metal interface controlled heterogeneous catalysis; the catalytic nanodiode

Abstract: Much of the research by KonradHayek's group is focused on the influence of oxide-metal interfaces in heterogeneous catalysis. In this paper, we show that electronic excitations at the metal surface induced by exothermic catalytic reactions lead to the generation of energetic (hot) electron flows. We detected the flow of hot electrons during oxidation of carbon monoxide using Pt/ TiO 2 Schottky diodes. The thickness of the Pt film used as the catalyst was 5 nm, less than the electron mean free path, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 26 publications
5
73
2
1
Order By: Relevance
“…Also, when vibrationally excited molecules strike another surface they are rapidly deexcited because of hot electron formation [42][43][44] . We fabricated a catalytic nanodiode where catalytically reactive platinum thin films were deposited on an oxide to form a Schottky barrier and we made contact to both sides of this barrier of Pt or Pd on TiO x or GaN [45][46][47] . Figure 18a shows the typical I-V curves measured on Pd/TiO x diode.…”
Section: The Active Sites At the Oxide Metal Interfacementioning
confidence: 99%
“…Also, when vibrationally excited molecules strike another surface they are rapidly deexcited because of hot electron formation [42][43][44] . We fabricated a catalytic nanodiode where catalytically reactive platinum thin films were deposited on an oxide to form a Schottky barrier and we made contact to both sides of this barrier of Pt or Pd on TiO x or GaN [45][46][47] . Figure 18a shows the typical I-V curves measured on Pd/TiO x diode.…”
Section: The Active Sites At the Oxide Metal Interfacementioning
confidence: 99%
“…As the surface becomes less positively charged, the acetonitrile orientation flips 180° with the CH 3 group pointing toward the surface. We constructed a so called catalytic nanodiode (59)(60)(61), which is composed of a metal of thickness less than the mean free path of hot electrons, deposited on a semiconductor surface, as shown in Figure 8a. When exothermic catalytic chemical reactions occur, we find that the heat transferred is converted to a hot electron flow that can pass through the metal film into the semiconductor which has a Schottky barrier (62; 63), which allows the passing of energetic electrons in one direction but not in the other direction.…”
Section: Future Directions Of Molecular Surface Sciencementioning
confidence: 99%
“…The oxide-metal interface is one of the major factors which determines the activity and selectivity of the heterogeneous catalysts [19][20][21] . It was observed that during certain reactions the oxide onto which the metal nanoparticles are deposited can dramatically change activity and selectivity even though the oxide itself is not active in catalysis 22,23 .…”
mentioning
confidence: 99%